Efektivitas penggunaan model pembelajaran PJBL berbasis deep learning & ICT terhadap peningkatan keterampilan berfikir kreatif pada pembelajaran PPKN siswa SD - Tri Wulandari; Sutrisna Wibawa (Universitas Sebelas Maret, 2025)
The development of 21st century technology has led to an increase in the need for education to be able to form humans who have productive personalities, are able to innovate and have higher creativity. Creative thinking is important for every student to have because it will be able to create new things during the learning process and solve various problems through ideas and ideas more broadly. The purpose of this study was to determine how much the effectiveness of the application of the project-based learning model or PJBL based on deep learning and ICT on improving students' creative thinking skills on Civics material at SD Negeri 3 Glodogan. This research was conducted using quasi-experimental method through one group pretest posttest design. The sample in this study was 6th grade students as one group used for research material on the application of the PJBL learning model. The instrument used in this research is an essay test instrument through indicators of creative thinking skills which are then further analyzed through quantitative testing. The result of this study is the use of project-based learning model based on deep learning and ICT is able to improve the creative thinking skills of each student. These results are shown by significant differences in the average acquisition of learning outcomes and the results of the analysis of thinking skills test both pretest and posttest. In addition, after the application of the project-based learning model, students were able to have a much higher creative thinking ability than before or in the category of more than 20% of their ability. For this reason, the use of project learning models has a very positive effect on increasing students' ability to think creatively.